ANALYSIS OF THE EFFECT OF PATIENT EXPERIENCE AND PATIENT SATISFACTION ON PATIENT LOYALTY - Rosally, Ruby Rizal; Ningrum, Shely Oktavia Puspita; Chalidyanto, Djazuly (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2024)
Hospitals have been competing to provide the best services in order to gain patient loyalty. Patient loyalty can be assessed from patient satisfaction and experience during hospitalization. This study aims to analyse the influence of patient experience and patient satisfaction on patient loyalty in the Outpatient Installation of Darmo Hospital. An analytical observational study using a cross-sectional approach was used in this study. The sample used in this study was 181 patients who were treated in the outpatient installation of Darmo Hospital Surabaya, selected using proportionate stratified random sampling technique. The independent variables in this study were patient experience and satisfaction, while the dependent variable was patient loyalty. Data was collected using a questionnaire and analyzed using logistic regression. The results showed a significant influence of patient experience on satisfaction (0.0001), patient experience on loyalty (0.0001), and satisfaction on loyalty (0.0001). Patient loyalty can be achieved by improving and enhancing patient experience, as better patient experience leads to increased patient satisfaction and loyalty towards the hospital. To gain patient loyalty, hospital services must be improved based on feedback in accordance with patients' wishes.